THE RELATIONSHIP OF KNOWLEDGE, EXPOSURE TO SUNLIGHT, AND CALCIUM INTAKE WITH THE RISK OF OSTEOPOROSIS - Erliza Anggraini Firdaus; Bambang Wirjatmadi (The Indonesian Journal of Public Health, 2020)
Osteoporosis is a bone disease causing decreased bone density. It often occurs to elderly women. At the age of 50-80 years, 23% Indonesian women were at risk of osteoporosis, and this number would increase to 53% at the age of 70-80 years. This study aimed to identify the relationship of knowledge, calcium intake and exposure to sunlight habits with the risk of osteoporosis. This study used a cross-sectional design involed 26 members of the osteoporosis gymnastic group who had a low and high risk of osteoporosis. Data of food consumption were retrieved from 24-hour food recall. The chi-square analysis shows knowledge level had a relationship with risk of osteoporosis (p=0.047). Exposure to sunlight (p=0.437) and calcium intake (p = 0.187) had a relationship with the risk of osteoporosis. It can be concluded that the level of knowledge had a significant relationship with risk of osteoporosis. Knowledge variable is important to show the community mindset about the dangers and risks of osteoporosis. Therefore, education about osteoporosis is required. Keywords: osteoporosis, knowledge, calcium intake, exposure to sunlight habits.